CTSA Search Solutions: A novel approach to searching CTSA hub website content - Barbara Tafuto; Riddhi Vyas; Trish Pruis (Journal of Clinical and Translational Science, 2022)
Clinical and Translational Science Award (CTSA) hub websites are a critical communication gateway to assist the clinical and translational science community and promote CTSA hub offerings. The objective of this funded pilot project was to create a website and online database for the CTSA consortium that allows users to conduct structured searches among the 50 + CTSA hub websites. The result is CTSA Search Solutions, an online, searchable database that includes access to 50 + CTSA hub websites with 80+ structured search term options and over 800 links collected, organized, and published. Hubs can be searched by name and filtered by a specific CTSA topic, state, region, or even number of years funded to make detailed comparisons with the data identified. The home page for each hub can be accessed directly from the search page. The CTSA Search Solutions online database will allow for a wide breadth of CTSA personnel (core leads, researchers, administrators, communicators, and evaluators) to find consolidated information to learn about specific CTSA hub program highlights, as well as conduct research into program hub outputs and best practices across the nationwide CTSA consortium.